Christianity and imperial culture : Chinese Christian apologetics in the seventeenth century and their Latin patristic equivalent - Wang, Xiaochao. (Studies in Christian Mission, 1998)
This book is a study of the writings of a group of Chinese Christian apologists in the seventeenth century, focussing on Xu Guangqi. Eleven of his shorter writings are included in Chinese and in translation. The first part of the book is devoted to a study of Latin Christian apologists within the Roman Empire to provide a comparison for the analysis of Xu Guangqi's work. Minucius Felix, Tertullian and Lactantius are shown to have faced, in regard to imperial power and Graeco-Roman culture, a situation comparable to that of Xu Guangqi, Li Zhizao and Yang Tinqyun in regard to imperial power and culture in the late Ming period. The final chapters of the book reconsider general issues of confrontation and adaptation in the inculturation of Christianity.